Ta’lim al-Qira’ah li al-Nathiqin bi Ghair al-‘Arabiyyah bi al-Nushush al-Ashliyyah al-Muhtawiyah ‘Ala al-Tsaqafah al-‘Arabiyyah - Faruq, Umar (Institut Agama Islam Negeri Curup, 2023)
This study aimed to propose strategies of how to teach Arabic reading comprehension by using materials taken from authentic sources. It employed a method that combined library research and field research. Library research was executed by searching authentic reading texts that were contextual and relevant with students’ needs, obtained from references, magazines, newspapers, and radio programs. All of which were written in by Arabic native speakers for Arabic native speakers. Field research was conducted by teaching Arabic reading comprehension using authentic materials in in the classroom. Implementing this method, it was found that teaching Arabic reading comprehension using authentic materials should be carried out in three stages: (i) pre-reading stage, conducted by facilitating students to understand the importance of authentic materials and negotiating the topics that the students were interested in; (ii) reading stage, in which students read and grasp texts through dialogues and group discussion guided by the teacher; and (iii) post-reading, in a way that the students did exercises by answering questions to sharpen their understanding about text contents. This practice of teaching Arabic reading provided such benefits as students were more motivated to study and more exposed to Arabic sentences having more complex and natural structures that were rarely found in simplified texts. Teacher’s guidance at each stage of learning was proven to be able to assist students in understanding the complex sentences. The significant contribution of this study is to overcome the weaknesses of using authentic materials as many studies have reported that authentic materials are frequently too difficult since they are beyond leaners’ language proficiencies. In addition, this research clearly confirms the theory of the importance of authentic materials in teaching a foreign language reading.